Synthesis of Barium Titanium Oxide Nanoparticles (International Journal of Food and Nutritional Sciences, 2022)
A new synthesis route to obtain high-purity barium titanium oxide nanoparticles,Ba2TiO4, using the microwave assisted solvothermal reaction of Barium acetate and Titanium tetrachloride solution in an oxygen atmosphere has been developed. The synthesized Ba2TiO4nanoparticles are nearly spherical in shape. Their grain sizes are determined by the Scherrer’s formula. The microstructure and composition of the as-synthesized samples were investigated by X-ray diffraction (XRD).